Evaluation of anti-epileptic properties of Evolvulus alsinoides by pentylenetetrazole-induced mouse model - Venkatesan, P. S.; Eswarya, M.; Madhavaselvi, M. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: A common neurological condition that affects people of all ages, epilepsy is defined by recurring seizures that have serious negative effects on the nervous system, cognition, psychology, and social interactions. Anti-epileptic drug (AED) side effects continue to be a significant concern despite advances in pharmacotherapy, as they can lower quality of life and adherence. Herbal medicines are becoming more and more popular as complementary and alternative therapies as a result. Methods: Using a mouse seizure model caused by PTZ (Pentylenetetrazole), this study examines the anticonvulsant efficacy of a traditional medicinal plant called Evolvulus alsinoides, often known as dwarf slender morning glory. The herb was mixed with 1.5% CMC and given to mice with various dosage levels. Results: The effects of various doses of morning glory extract (50 mg/kg to 400 mg/kg body weight) on latency period and seizure duration were compared to those of a control group and a diazepam-treated group. In latency period, 300 mg/kg. b. wt group showed a long latency period of 222.5±47.68 (p<0.05) when comparing to other groups. Morning glory of dose 400 mg/kg b. wt eliminated tonic-clonic seizures in all animals (p<0.001). Conclusions: These findings suggest that Evolvulus alsinoides has anti-epileptic properties in PTZ-induced mice model.